Pengaruh Konsumsi Pisang Ambon Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi Di Wilayah Kerja Puskesmas Tebing Tanjung Balai Karimun - Wibawa Fazsli; Rizki Sari Utami Muchtar; Sri Muharni (Jurnal Ventilator, 2024)
The most common health problem suffered by the elderly is hypertension. In Indonesia, hypertension is in first place with the most problems experienced by the elderly, followed by arthritis, diabetes mellitus, heart disease and stroke. One non-pharmacological treatment that can be done is consuming Ambon bananas twice a day for 7 days. Objective: This research is to determine the effect of Ambon bananas on reducing blood pressure in elderly people with hypertension in the Tebing Tanjung Balai Karimun health center working area. This research design uses a Group Experimental with a Quasy Experiment design using a One Group Pretest and Posttest Design. The respondents in this study were 30 respondents divided into 15 intervention groups and 15 control groups. The sampling technique used was purposive sampling. Results: statistical paired sample t test showed p value = 0.000 (< 0.05) so Ho was rejected. This shows that there is an influence of consumption of Ambon bananas on reducing blood pressure in the intervention group. Conclusion: with this research, consumption of Ambon bananas can be used as a non-pharmacological therapy to lower blood pressure. Suggestion: Respondents should always apply non-pharmacological walking exercises to control blood pressure.